Constructivist Strategies Used by Miss Honey in Roald Dahl's Matilda - Kadek Leny Mahendrayani; Ni Komang Arie Suwastini; Ida Ayu Made Istri Utami; Nice Maylani Asril; Zhu Minxia (Journal of Psychology and Instruction, 2025)
The novel as a work of literature may contain beneficial insights, including pedagogical philosophies. The present study aimed to discover constructivist teacher strategies used by Miss Honey, the teacher character in Roald Dahl's Matilda. Through qualitative method enriched with the constructivist perspective, the study revealed that Miss Honey employed eight constructivist strategies as an elementary school teacher in her class. The first strategy was encouraging students' autonomy and initiative by letting them try reading a long sentence on the blackboard before giving examples of how to read them. The second strategy was the use of primary and physical materials as the source of manipulative and interactive materials, such as exercise books, poetry books, and posters. The third strategy involved inviting the students' responses during the learning activities and making them active. The fourth strategy was allowing the students to construct their conceptual knowledge before concluding it. The fifth strategy was encouraging teacher-students and peer dialogues. Miss Honey also trained students' cognition by using open-ended questions. Besides, Miss Honey also sought elaboration of students' initial responses to cultivate their reasoning. The last constructivist strategy implemented by Miss Hone was allowing the students to think after posing questions to construct their opinions. These findings imply that the novel can be a good reading material for elementary school teachers to illustrate how to implement constructivist strategies in a beginner class.